Pengaruh Perdagangan Internasional dan Investasi Asing Langsung terhadap Pertumbuhan Ekonomi di 5 Negara ASEAN Tahun 2015-2024 dalam Perspektif Ekonomi Islam - Lisa Septina; Sania Nuraziza; Erlin Kurniati (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
This study aims to analyze the effect of international trade and foreign direct investment on economic growth in five ASEAN countries, namely Indonesia, Malaysia, Singapore, the Philippines, and Thailand, from 2015 to 2024 from an Islamic economic perspective. Using a descriptive quantitative approach with secondary data obtained from the World Bank, the analysis was conducted using panel data regression with the Fixed Effect Model (FEM). The results of the study indicate that international trade has a positive and significant effect on economic growth, while foreign direct investment has a positive but insignificant effect on economic growth. Simultaneously, both variables have a significant effect on economic growth. From an Islamic perspective, trade that complies with Sharia principles, such as freedom from usury, gharar, and maysir, is encouraged. In line with this, Islam also supports investment because, according to its teachings, wealth should not be hoarded but must be used in a beneficial and productive manner.